The Effect of Audiovisual Counseling of Conception Period and Nutrients to the Nutrient Improvement Motivation on Pregnant Mothers at Primary Health Center Girisubo Gunungkidul Yogyakarta in 2015 - Indah Puspitasari, A; Satriyandari, Y (KnE Life Sciences, 2019)
Malnutrition on pregnant mothers is the highest health problem in the world. From a hundred and forty-two pregnant mothers at primary health center Girisubo, 73 cases (51.4%) had chronic energy deficiency, and 26 cases (18.3%) had anemia on trimester I and III. The purpose of this study was to investigate the effect of audiovisual counseling of conception period and nutrients to the nutrient improvement motivation on pregnant mothers at the primary health center of Girisubo Gunungkidul Yogyakarta in2015. The study employed the True Experimental Design with pretest-posttest control group design. The research population was 35 pregnant mothers. The samples were 30 people taken through simple random sampling. The samples were divided into two groups. Fifteen people were in the experiment group, and 15 people were in the control group. The data analysis used Wilcoxon and Mann-Whitney U-test. The pregnant mother’s nutrient improvement motivation on experiment group shows that 73.3% of respondents were in medium category in pretest and this number increased to 80% in posttest for good category. The Wilcoxon test obtained p-value 0.000. The result on the experiment group shows that 86.6% were in medium category in pretest and 53.3% were in medium category in posttest with p-value 0.001. There is an effect of audio visual counseling of conception period and nutrients to the nutrient improvement motivation on pregnant mothers at Primary Health Center Girisubo Gunungkidul Yogyakarta in 2015. Audio visual media could be used in counseling as an effort to improve pregnant mother’s motivation to care for pregnancy. Keywords: counseling, audiovisual, conception, nutrients, and pregnant mothers